Household Waste Pollution and Dilemma in Society Based on Law Number 32 of 2009 Concerning Environmental Protection and Management - Sumarno, Sumarno; Ismaidar, Ismaidar (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
Enforcing Law Number 32 of 2009 concerning Environmental Protection and Management in household waste management. The increasing accumulation of household waste and low public legal awareness have led to environmental pollution. The gap between legal norms and social realities influences structural and cultural factors, as well as weak law enforcement at the village level. The social dilemma arises when people are aware of the impacts of pollution but continue to litter due to practical and economic considerations. Recommendations for strengthening community participation, establishing waste management units, developing circular economy-based waste banks, and providing ongoing legal and environmental education are recommended. These findings emphasize the importance of transforming legal norms into living laws through synergy between the government and local communities.